Cytologic effects of primary tooth endodontic filling materials - Tsui-Hsien Huang; Chi-Jr Hung; Yi-Jyun Chen; Hung-Chih Chien; Chia-Tze Kao (Elsevier, 2009)
Primary tooth endodontic filling materials should be bio-compatible with periodontal tissue. The purpose of this study was to analyze the biologic effects of different endodontic filling materials for primary teeth on a human osteosarcoma cell line (U2OS). Materials and methods: Experimental groups comprised different mixes of endodontic filling materials: zinc oxide-eugenol (ZnOE) + formocresol (FC); calcium hydroxide [Ca(OH)2] + FC; Ca(OH)2 + iodoform + deionized water; Ca(OH)2 + iodoform +camphorated parachlorophenol (CPC); Ca(OH)2 + CPC; and Vitapex. These were prepared and used to fill special glass rings, which were subsequently eluted in 10 mL of cell culture medium at 37ºC in a 5% carbon dioxide-in-air atmosphere for 24 hours. Cell culture medium alone was used as the control group. A DNA fragmentation assay was performed to determine the genotoxicity of each mix of materials. The level of cyclooxygenase (COX)-2 protein expression, the extent of dental material-elicited inflammation of U2OS cells, and the degree of mitogen-activated protein (MAP) kinase expression were determined using Western blot analysis. Results: The results revealed that no DNA breakage was apparent after U2OS cells were treated with the various materials. COX-2 band expression dramatically declined in the ZnOE + FC group compared with the control group, although high levels of expression of the COX-2 band were noted for the Ca(OH)2 + FC and Ca(OH)2 + iodo-form + CPC groups. Band levels of extracellular signal-regulated kinase (ERK-1 and ERK-2) expression declined in the ZnOE + FC and Ca(OH)2 + CPC groups compared with the control group. p53 and caspase-3 protein bands appeared in all experimental groups. Conclusion: The cytotoxic mechanism of endodontic filling materials on U2OS cells was induced by means of activation of the p53 and caspase-3 apoptosis signaling pathways.